2002
DOI: 10.1021/bm020056g
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Dynamic Light Scattering of Silk Fibroin Solution Extracted from the Middle Division ofBombyx moriSilkworm

Abstract: Dynamic light scattering (DLS) and rheological measurements were performed on aqueous silk fibroin solutions extracted from the middle division of Bombyx mori silkworm over a wide range of polymer concentration C from 0.08 to 27.5 wt %. DLS results obtained in the dilute region of C less than 1 wt % are consistent with a model that an elementary unit is a large protein complex consisting of silk fibroin and P25 with a 6:1 molar ratio. Rheological measurements in the dilute C region reveal that those units (or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 67 publications
13
107
2
Order By: Relevance
“…The calcium ions were probably stabilized on the ␤-sheet structure of the silk fibroin. 48,49 In this study, the addition of calcium ions increased the portion of ␤-sheet structure. The calcium ions, however, were not tightly bonded to the ␤-sheet structure, as they eluted rapidly from the SFFs.…”
Section: The Effect Of Soaking Time On Hydroxyapatite Depositionmentioning
confidence: 53%
“…The calcium ions were probably stabilized on the ␤-sheet structure of the silk fibroin. 48,49 In this study, the addition of calcium ions increased the portion of ␤-sheet structure. The calcium ions, however, were not tightly bonded to the ␤-sheet structure, as they eluted rapidly from the SFFs.…”
Section: The Effect Of Soaking Time On Hydroxyapatite Depositionmentioning
confidence: 53%
“…Previous studies have shown that the silk fibroin is present in the dilute solution as aggregates (or clusters) composed of several large protein complexes, which presumably are induced by hydrophobic interactions among the hydrophobic parts of the fibroin chains. [28][29][30] Comparable to typical amphoteric block copolymers, the aggregation of silk fibroin in the solution is probably easier when its molecule distributes in a narrower and higher region.…”
Section: Full Papermentioning
confidence: 99%
“…23,24 Generally, it is believed that hydrophobic/hydrophilic block copolymer structures may be assembled into β-crystallites via the nanofibrillar cross-linked network of the silk fibroin in solution ( Figure 1c). [24][25][26][27] Analysis of the particle size distribution and zeta potential showed that the silk fibroin in the solution underwent aggregation when the temperature of the solution increased (Figure 1d). This behavior probably involves interaction with Fe 3+ , and thus the silk fibroin acts as a template for crystallization.…”
Section: Resultsmentioning
confidence: 99%